Towards an Understanding of Drone Fiction. (2nd January 2019) - Smethurst, Tobi; Craps, Stef
Abstract : Since the end of the twentieth century, strike-capable military drones have rapidly evolved from an ominous near-future technology, seldom discussed outside of science fiction or top-secret military contexts, to a burgeoning multi-billion dollar international industry at the centre of public scrutiny and interest. Meanwhile, the figure of the drone has saturated Western public consciousness to the point that it can be described as a trope. Sparking the interest of artists, writers, and filmmakers, drone warfare has begun to feature in a wide range of films, books, and art installations, and this flood of drone-related media seems unlikely to peter out. To date, however, little academic work has looked in depth at cultural interpretations of drones and the role they serve in fictional(ized) narratives. What is urgently needed to better our understanding of the drone, we argue, is a cultural studies perspective that is able to assess the drone as a fictional, narrative construct, while still taking account of its very real, material consequences for both pilots and victims. This article aims to introduce readers to the nascent field of drone fiction, providing a jumping-off point for future research into the figure of the drone. Here, we explore how drone warfare is mediated through three different drone-fictional works: the semi-autobiographical book The Drone Eats with Me by Atef Abu Saif, the experimental video game Unmanned by Molleindustria, and the short film 5, 000 Feet Is the Best by Omer Fast. Through close readings of these varied works, we draw attention to what each particular mode of mediation reveals about the effects of drones on those who work with or live around them.